(untitled) (Third Sector Social Economic Review, 2019)
This study aims to evaluate “holiday effect” for stocks traded at BIST Banking index during 03.01.2013-30.09.2018 period. In this context, at least three-day-long religious and national holidays with no transaction, whether or not involving weekends, are determined. Investigation of any anomaly is not limited with the last transaction days before and first days after holidays but extended till the fifth day before holidays. Results suggest that holiday effect is exists for a number of bank stocks and the anomalies occur especially the 2.-5. days before holidays